되새김 증후군 환자에 대한 한방치험 1례 - 조임학; 서형범; 이찬; 강희경; 허기윤; 권정남; 박성하; 윤영주; 이인; 최준용; 한창우; 홍진우; et al. (대한한방내과학회지, 2020)
Objectives: This study presents a case of a 53-year-old Korean male with rumination after meals. The aim was to assess the effectiveness of Korean medical treatment. Methods: The outpatient was treated with acupuncture, electroacupuncture, and herbal medicine (Hwangryun-tang, Hyangsapyungwi-san-gami, Anjung-san granules, and Hyangsapyungwi-san granules) for 3 months. We evaluated the patient's symptoms whenever he visited the clinic. Results: The patient showed significant improvements after Korean medical treatment. In particular, regurgitation of food disappeared after herbal medicine treatment. Conclusions: This case report suggests that Korean medical treatment could be effective in treating rumination syndrome. Further studies are needed.